Populism, authoritarianism and constitutionalism - Gábor Halmai (German Law Journal, 2019)
The paper deals with the relationship of different types of populism with authoritarianism and constitutionalism. In the first part, I try to define various approaches—Left and Right-Wing, “good” or “bad”—to populism, especially from the point of view of whether they aim at changing the liberal democratic constitutional system to an authoritarian one. The following part discusses the rhetoric of authoritarian populists, which makes this type of populism distinct from non-populist authoritarians. The paper also explores the question of whom to blame for the success of authoritarian populisms, and the final part investigates, whether the use of legal tools by an authoritarian populist to dismantle liberal constitutional democracies means that we can speak about a special populist constitutionalism. While the paper tries to find out the joint characteristics of authoritarian populism, it heavily relies on the Hungarian experiences as a kind of model approach in East-Central Europe and maybe even beyond.